The Mum - Minder - Wilson, Jacqueline (London : Corgi Books, 2009)
I'm Sadie and I'm nearly nine. Mum's a childminder, but she doesn't have to mind me. I can mind myself, easy-peasy.
Keywords: Mothers and doughters -- Fiction